Academic Procrastination and Negative Emotions Among Adolescents During the COVID-19 Pandemic: The Mediating and Buffering Effects of Online-Shopping Addiction - Wang, Qiaoling; Kou, Ziyu; Du, Yunfeng; Wang, Ke; Xu, Yanhua (Frontiers in Psychology, 2022)
Purpose: The COVID-19 pandemic that began in 2019 has had a significant impact on people’s learning and their lives, including a significant increase in the incidence of academic procrastination and negative emotions. The topic of how negative affect influences academic procrastination has been long debated, and previous research has revealed a significant relationship between the two. The purpose of this study was to further investigate the mediating and buffering effects of online-shopping addiction on academic procrastination and negative emotions. Methods: A total of 423 students, 118 males (27.9%) and 305 females (72.1%) from 10 vocational and technical colleges in Guangdong were surveyed using online-shopping-addiction scale, academic-procrastination scale and negative-emotions scale. The researchers conducted a correlation analysis followed by a mediation analysis and developed a mediation model. Results: The results showed that: first, academic procrastination was significantly and positively associated with online-shopping addiction (r = 0.176, p < 0.01). Second, academic procrastination was significantly and positively associated with negative affect (r = 0.250, p < 0.01). Third, online-shopping addiction was significantly and positively associated with negative affect (r = 0.358, p < 0.01). In addition, academic procrastination had a significant positive predictive effect on online-shopping addiction ( β = 0.1955, t = 3.6622, p < 0.001). Internet-shopping addiction had a significant positive predictive effect on negative emotions ( β = 0.4324, t = 7.1437, p < 0.001). Conclusion: This study explored the relationship between students' academic procrastination, negative emotions, and online-shopping addiction during the COVID-19 pandemic. The results indicated that students’ level of academic procrastination positively influenced their level of online-shopping addiction and negative emotions, and their level of online-shopping addiction increased their negative emotions. In addition, there was a mediating effect between the degree of participants’ online-shopping addiction and their degree of academic procrastination and negative emotions during the pandemic. In other words, with the mediating effect of online-shopping addiction, the higher the level of a participant’s academic procrastination, the more likely that the participant would have a high score for negative affect.